PENGEMBANGAN MODEL PEMBELAJARAN KUANTUM KOOPERATIF UNTUK MENINGKATKAN KETERAMPILAN MEMBACA DONGENG PESERTA DIDIK SEKOLAH DASAR - Tugimin Tugimin (Pendidikan Bahasa dan Sastra Universitas Muhammadiyah Purworejo, 2014)
ABSTRACT: This Research background is lowering skill read educative by participant fable elementary school. Its problem is how requirement, model characteristic, especial product prototype, and accepability model study of co-operative quantum to increase ability read fable at educative. Target of this research of requirement description, model characteristic, product prototype, and aquntability of development model study of co-operative quantum to increase ability read fable at educative. Theory model study according to Joice, et all, theory study of quantum which is descreption by dePorter, theory study of developed by co-operative is Judge, and theorys which is relevant to solve problem. type Research of development with procedure (1) antecedent study, ( 2) development phase, and (3) diskription result of research. Result of research cover (1) existence of requirement of development model study of co-operative quantum, (2) characteristic model expected by study for example, can grow is same activity, giving freedom room for the creativity, to lessening educative betwen students achievement difference, educative by participant of adjacent obtained flattened, study take place to please. ( 3) especial product in the form of model desain, and model peripheral ( 4) expert team validity product here in after try out limitedly. Pursuant to result of research suggested, teacher shall use the model product for the uplifting of skill of to read. Key word: model, quantum, co-operative, skill, reading fable. ABSTRAK: Latar belakang penelitian ini adalah rendahnya keterampilan membaca dongeng siswa sekolah dasar. Masalahnya, bagaimanakah kebutuhan akan pengembangan model, karakteristik model, prototipe produk utama pengembangan model, dan keberterimaan model pembelajaran kuantum kooperatif untuk meningkatkan kemampuan membaca dongeng peserta didik kelas V sekolah dasar. Tujuan penelitian ini mendeskripsikan kebutuhan akan pengembangan model, karakteristik model, prototipe produk, dan keberterimaan pengembangan model pembelajaran kuantum kooperatif. Jenis penelitian adalah penelitian pengembangan dengan prosedur (1) studi pendahuluan, (2) tahap pengembangan, dan (3) diskripsi hasil penelitian. Studi kebutuhan dilaksanakan di empat sekolah yang berada diwilayah Kecamatan Kepil dengan ketentuan dua hal, yakni (1) sekolah negeri dan swasta, (2) sekolah berprestasi rendah, berprestasi sedang, dan berprestasi tinggi. Hasil penelitian meliputi (1) adanya kebutuhan pengembangan model pembelajaran kuantum kooperatif, (2) karakteristik model pembelajaran yang diharapkan antara lain, mampu menumbuhkan kerja sama yang positif, memberi ruang kebebasan untuk berkreativitas, mengurangi kesenjangan prestasi antarpeserta didik, peserta didik memporeleh pendam-pingan secara merata, pembelajaran berlangsung menyenangkan. (3) produk utama berupa desain model, dan perangkat model (4) produk divalidasi tim ahli selanjutnya diujicobakan secara terbatas. Berdasarkan hasil penelitian disarankan, guru hendaknya menggunakan produk model tersebut untuk peningkatan keterampilan membaca peserta didiknya. Kata kunci: model, kuantum, kooperatif, keterampilan, membaca dongeng